Early Children Character Education: Analysis of The Message of The Quran in Forming Human Morality - Zaitun Zaitun; Pipin Armita; Mohd Faizulamri Mohd Saad (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2023)
Character education is important to instill in early childhood. The purpose of this research is to see the concept of character education for early childhood from the perspective of the Qur'an. The importance of education is not only found in the perspective of national education but also in the Qur'an, which leads to the formation of human morality. The method used in this study was by conducting library research. This descriptive research used a qualitative approach. Simultaneously, the data analysis technique applied content analysis by emphasizing the constancy of the content of communication, the meaning of the content of communication, the reading of symbols, and the meaning of the contents of the interaction of symbols in communication. The results of this study show that the Qur'an pays attention to education to shape the morale of early childhood and Muslims so that they become a person with a strong character. The novelty in research is that the Qur'an has outlined character education for early childhood by forming human morals through a) education and science (Q.S al-Baqarah: 266), b) cultivation of faith (Q.S an-Nisa: 59), and c) implementation of the Shari'a (Q.S al-Ankabut: 45). The implication of this research is that it can be applied as the main principle in Islamic education to shape the character of early childhood and as an effort to reorient the concept of Islamic education contained in the Qur'an.